Particle production as a function of charged-particle flattenicity in pp collisions at s =13 TeV - Acharya, S.; Adamovã, D.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; et al. (American Physical Society, 2025)
This paper reports the first measurement of the transverse momentum ( p T ) spectra of primary charged pions, kaons, (anti)protons, and unidentified particles as a function of the charged-particle flattenicity in pp collisions at s = 13 TeV . Flattenicity is a novel event shape observable that is measured in the pseudorapidity intervals covered by the V0 detector, 2.8 η 5.1 and − 3.7 η − 1.7 . According to QCD-inspired phenomenological models, it shows sensitivity to multiparton interactions and is less affected by biases toward larger p T due to local multiplicity fluctuations in the V0 acceptance than multiplicity. The analysis is performed in minimum-bias (MB) as well as in high-multiplicity events up to p T = 20 GeV / c . The event selection requires at least one charged particle produced in the pseudorapidity interval | η | 1 . The measured p T distributions, average p T , kaon-to-pion and proton-to-pion particle ratios, presented in this paper, are compared to model calculations using 8 based on color strings and EPOS LHC. The modification of the p T -spectral shapes in low-flattenicity events that have large event activity with respect to those measured in MB events develops a pronounced peak at intermediate p T ( 2 p T 8 GeV / c ), and approaches the vicinity of unity at higher p T . The results are qualitatively described by , and they show different behavior than those measured as a function of charged-particle multiplicity based on the V0M estimator.
Keywords: Physics; Pseudorapidity; Particle physics; Charged particle; Ion; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03